Pengaruh Pertumbuhan Ekonomi Terhadap Kemiskinan Di Provinsi Nusa Tenggara Barat: Perspektif Ekonomi Islam - Afifudin Afifudin; Tati Atmayanti (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This study aims to determine how the effect of economic growth on poverty levels in the province of NTB. The analytical tool used is simple linear regression using secondary data sourced from NTB Bps. The independent variable is NTB Province economic growth and the poverty variable in NTB province as the dependent variable. The results of this study are that economic growth variables have a positive and significant effect on poverty in the NTB Province, meaning that the higher the economic growth of the NTB Province will increase the number of poor people in the NTB Province. This result means that not all NTB people have enjoyed economic growth and only enjoyed a portion of the NTB community. Furthermore, in the Islamic perspective that the management of zakat has not been maximized as a supporter of the people's economy.